Discussion on the Waterproof and Drainage System of the Coastal Tunnel and Analysis of Water Pressure Law outside Lining: A Case Study of the Gongbei Tunnel. (27th February 2021) - Zhao, Jinpeng; Tan, Zhongsheng; Zhou, Zhenliang
Abstract : With the orderly promotion of the infrastructure construction in China, the number of coastal tunnels is increasing, but the coastal environment is accompanied by a large amount of groundwater and the designs of the waterproof and drainage system of coastal tunnels have always been a hot topic in the industry. If the waterproof and drainage system designs of the coastal tunnels are improper, the tunnel structure will easily be damaged and the stability and service life of the whole project will be affected. Based on the Gongbei tunnel project of the Hong Kong-Zhuhai-Macao Bridge, this paper discusses the designs of the waterproof and drainage system, and the waterproof detail structures of the Gongbei tunnel. Indoor similarity tests were carried out to study the law of the free water discharge of the tunnel under variable water heads, the relationship between the water pressure outside the lining and the water discharge, the relationship between the water pressure outside the pipe roof and the water discharge, and the distribution of water pressure around the tunnel. The reliability of the indoor similarity test was verified by the field test. The results show that the whole waterproof system should be adopted in the Gongbei tunnel, that is, grouting ring + pipe roof freezing ring + initial lining + waterproof board + tertiary lining. In a certain range, the greater the water head, the greater the free water discharge of the tunnel. When the water head is large, the free drainage tends to a fixed value. When the tunnel is completely plugged, the water pressure outside the tunnel is distributed from the hydrostatic pressure. When the tunnel adopts drainage measures, the water pressure outside the lining will be reduced to a certain extent even the water discharge is very small. The above research can provide a reference for the design of the waterproof and drainage system similar to the coastal tunnel in the future.